Adhesion molecule expression in primary sclerosing cholangitis and primary biliary cirrhosis. Issue 4 (April 1995) - Bloom, S; Fleming, K; Chapman, R
Abstract : There are conflicting reports regarding intercellular adhesion molecule-1 (ICAM-1) expression in primary sclerosing cholangitis (PSC) and primary biliary cirrhosis (PBC). Expression of adhesion molecules ICAM-1, lymphocyte adhesion molecule-1 (LFA-1), vascular cell adhesion molecule (VCAM), and E-selectin was examined together with HLA-DR in 16 liver biopsy specimens showing PSC and 12 specimens showing PBC. These were compared with biopsy specimens showing large duct obstruction (n = 7), chronic active hepatitis (n = 4), alcoholic liver disease (n = 4), and normal liver histological results (n = 5). ICAM-1 was detected on biliary epithelium in five of seven PSC specimens of histological stage 3 or 4, but not in nine early PSC specimens or in specimens from disease controls. In PBC, ICAM-1 was positive on three of 12 cases, two stage 2, and one stage 3. Nine of 16 PSC specimens (three of nine early, six of seven late disease) and six of 10 PBC specimens (three early, three late disease) were positive for HLA-DR. LFA-1 stained infiltrating inflammatory cells in PSC, PBC, and disease controls. In conclusion, ICAM-1 expression on biliary epithelium in PSC occurs mainly in late stage disease and therefore may be secondary to previous events inducing inflammation rather than of primary pathogenic importance. ICAM-1 expression in PBC is less common and not clearly associated with a particular disorder. Previous reports of ICAM-1 prevalence may have been biased towards end stage, pre-transplantation biopsy specimens.